Midface fracture - Denia Morales Navarro (Editorial Ciencias Médicas, 2018)
Introduction: midface fractures are a serious medical problem due to their complexity, frequency and socioeconomic impact. Objective: conduct a literature review about the anatomical considerations, diagnosis, classification, treatment and complications of midface fractures. Methods: A literature review was conducted in September 2016. The evaluation included high impact journals from the Web of Science (25 journals) and 2 books. The databases MEDLINE, PubMed and SciELO were consulted, using the descriptors "maxillary fracture", "treatment", " lefort fracture". Papers written in English in the last five years were included. Of the 98 papers obtained, the study considered 40. Data analysis and integration: the middle third of the face is characterized by anatomical weakness, since it is formed by scantily protected spongy bone with multiple sutures. There are many classifications for midface fractures, and diagnosis is based on clinical findings, particularly ophthalmological, which alongside those of auxiliary diagnostic devices, make it possible to choose the most appropriate therapeutic mode and prevent complications. Conclusions: the anatomical characteristics of the facial middle third justify the frequency and impact of these fractures. Diagnosis should be based on interrogation, physical examination and the use of auxiliary diagnostic imaging, mainly tomography. Upon classification of the fracture, a treatment plan may be devised based on individual assessment of each case to prevent future complications.